Intra-Peritoneal Rectal Perforation in a Neonate Leading to Acquired Rectal Atresia - Yogesh Kumar Sarin (EL-Med-Pub, 2013)
A neonate sustaining iatrogenic rectal injury that led to acquired rectal atresia is reported. It was successfully treated by transanal, end-to-end, rectorectal anastomosis.